Agregacja budżetów kosztów wspomagana MS Excel - Kujawski, Jarosław (MS Excel-Aided Aggregation of Cost Budgets, 2007)
The paper presents a concept of MS Excel - aided system of cost budgets aggregation. The core assumptions of the concept are: an identical layout of all cost budgets, blocking the cost positions that are not available to be budgeted and the application of special global sum function built in the spreadsheet. The Automated summing of budgets is not obstructed by adding newly-created or cutting unnecessary budgets thanks to the dedicated mechanism of sheets and file management. The presented IT tool has been tailor-made to the medium-sized enterprise operating in the electro-mechanics sector. It makes possible for 14 responsible persons to manage 31 budgets of 30 MB disk memory.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 332-343